Transformasi Sosial-Ekonomi Keluarga Rentan melalui Edukasi dan Aksi Partisipatif Jemaat Gereja Bethel Indonesia Tumbang Rungan Palangka Raya - Sarmauli, Sarmauli; Mariani, Evi; Bate’e, Yamowa’a; Tanyid, Maidiantius; Binoto, Parluhutan Dodo; Oktavia, Eni; Punghendarto, Ade Septa; Jayanti, Kusuma (Civiliza Publishing, 2025)
The implementation of Community Service (PKM) aims to carry out socio-economic transformation of vulnerable families through education and participatory actions of the congregation of the Indonesian Bethel Church (GBI) Tumbang Rungan Palangka Raya. Congregation members who fall into the category of socio-economically vulnerable families need to receive special attention from the church. This special service is a form of needs-based service, which focuses not only on spiritual services but also on education and economics. The specific targets of this PKM are: (1) Providing an understanding of the congregation about the importance of Socio-Economic Transformation, (2) Providing social education and economic literacy training for vulnerable families in GBI Tumbang Rungan, and (3) Increasing the role and participatory actions of the Congregation in GBI Tumbang Rungan. The proposed activity plan includes a series of workshops and focus group discussions to identify the socio-economic needs of vulnerable families, conducting education and congregation participation adapted from the results of the workshops, and evaluating the impact of this program on congregation attendance at Sunday services. This study used the Participatory Action Research (PAR) method, which actively involved the congregation in the planning, implementation, and evaluation of the program. With this approach, it is hoped that the socio-economic transformation program for vulnerable families, through education and participatory action by the GBI Tumbang Rungan Palangka Raya congregation, will improve their well-being and strengthen their bond with the church community. Keywords: Socio-Economic Transformation, Vulnerable Families, Education and Participatory Action of the Congregation, GBI Tumbang Rungan.